2017
DOI: 10.7189/jogh.07.020507
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal care for newborns in Bangladesh: The importance of health–related factors and location

Abstract: BackgroundBangladesh achieved Millennium Development Goal 4, a two thirds reduction in under–five mortality from 1990 to 2015. However neonatal mortality remains high, and neonatal deaths now account for 62% of under–five deaths in Bangladesh. The objective of this paper is to understand which newborns in Bangladesh are receiving postnatal care (PNC), a set of interventions with the potential to reduce neonatal mortality.MethodsUsing data from the Bangladesh Maternal Mortality Survey (BMMS) 2010 we conducted l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 24 publications
2
22
2
Order By: Relevance
“…4 Though asphyxia is caused due to poor maternal health condition or complications during labor, newborn asphyxia would be treatable if postpartum mother and their newborns receive first-aid healthcare during or after labor. 5 It has been reported that some basic and effective resuscitation can save majority of newborns who develop asphyxia. 6 However, many newborn babies are suffered from asphyxia deprived of receiving adequate resuscitative care in the developing world and because of the limitations in skilled providers who know how to use simple resuscitation methods and equipments.…”
mentioning
confidence: 99%
“…4 Though asphyxia is caused due to poor maternal health condition or complications during labor, newborn asphyxia would be treatable if postpartum mother and their newborns receive first-aid healthcare during or after labor. 5 It has been reported that some basic and effective resuscitation can save majority of newborns who develop asphyxia. 6 However, many newborn babies are suffered from asphyxia deprived of receiving adequate resuscitative care in the developing world and because of the limitations in skilled providers who know how to use simple resuscitation methods and equipments.…”
mentioning
confidence: 99%
“…This high dropout could be explained by different reasons like: cultural barriers [13,[50][51][52], dissatisfaction from previous service [52], and autonomy to receive health service [13]. A possible further explanation for the low use of PNC might be also due to low level of awareness about the importance of the service even when there are no complications after birth [6,10,13,28,31,46].…”
Section: Discussionmentioning
confidence: 99%
“…Literature yields that age, wealth status, ability to communicate with health care providers, and the existence of health complications [7,13,[28][29][30][31]. Cultural and social norms also inhibit young to ask, obtain information, discuss and express their worries about sexual and reproductive health issues because it is often considered as taboos to discuss sexuality issues with families or community members [30,32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence shows that use of MNH services is influenced by myriad socio-demographic, health service-related, and cultural factors [16][17][18][19][20][21][22][23][24][25][26]. Multiple studies find maternal age, parity, lack of time, education, marital status, women's economic status, residence, and distance to health facility are significant predictors of use of maternity care services [16,18,27,28]. Accordingly, intervention strategies targeting improved use of MNH services should address both supply-and demand-side factors.…”
Section: Introductionmentioning
confidence: 99%